EXPLORATION OF ETHNOMATHEMATICS ON THE WOODEN KELINTANG MUSICAL INSTRUMENT - Rajwa Mayyaza; Rima Meslita; Tia Agnesa (Universitas Muhammadiyah Lampung, 2026)
This study aims to explore the ethnomathematics found in traditional Jambi musical instruments, especially wooden kelintang musical instruments. This type of research is a descriptive qualitative research using an ethnographic approach (socio-cultural) with data sources obtained from observation, interview, and documentation methods. Data analysis in this study uses the Spradley model analysis in Lexy J. Maleong including domain analysis, taxonomy analysis, component analysis, theme analysis. To check the validity of the data, the author uses the triangulation technique. This research was conducted at the Mindulahin Studio in Jambi City. The results of the study can be concluded that: 1) The mathematical concepts found in wooden kelintang musical instruments include: Flat shapes in the form of rectangles, circles, and trapezoids. Space shapes in the form of blocks, cylinders, angles in the form of 90 °, relations and functions, and arithmetic. 2) Ethnomathematic activities in wooden kelintang include activities of calculating, measuring, determining locations, making designs, playing, and explaining. All these activities can be seen from how to make wooden kelintang, the shape of the wooden kelintang, and when playing the wooden kelintang.